A shared heritage: The origin and use of textile patterns in Himalaya and Tibet - Bangsbo, Ellen (Archaeological Textiles Review, 2023)
The article addresses the origin, use and exchange of patterns in Himalayan textiles. Ancient designs and patterns travelled with merchants and pilgrims, covering large distances from Rajasthan and Gujarat in India and ancient Iran to be used, copied and exchanged in ancient Central Asia and Himalaya. While textiles decompose and we are left with few remains of ancient times, textile designs and patterns are fully present in paintings on ceilings, walls, beams and sculptures in 11th century CE temples in Northern India, places with predominantly Tibetan culture. These patterns and designs are still in use in present-day textile heritage and handicrafts in Himalaya and on the Tibetan plateau, ranging from Ladakh in the west to Bhutan in the east.